Efektivitas Program Literasi Digital Berbasis Smart Society 5.0 Pada Dinas Komunikasi Dan Informatika Kabupaten Ciamis - Puji Lestari; Sisi Kurli Oktrimayunda; Istianatullaila Istianatullaila; Nida Nurpadilah; Irfan Nursetiawan (Universitas 17 Agustus 1945 Semarang, 2024)
The digital literacy level in Indonesia is only 62%. This number is the lowest compared to other ASEAN countries, which average 70%. Therefore, acceleration is needed to catch up with digital literacy levels in various regions in Indonesia, including Ciamis Regency. This needs to be done to encourage people to avoid all types of technological fraud and to be better prepared to face the digital era in the future. This research aims to evaluate the effectiveness of the digital literacy program launched by the Ciamis Regency Communication and Information Service (Dinas Komunikasi dan Informatika ) based on the Smart Society 5.0 concept. This research method uses descriptive data collection techniques through literature, interviews and related data analysis. The research results show that the Smart Society 5.0-based digital literacy program by the Ciamis District Communication and Information Office has had a positive impact in increasing people's understanding of digital technology, expanding access to information, and encouraging active participation in digital life. However, there are several obstacles faced, such as limited access to digital infrastructure, lack of public awareness of the importance of digital literacy, and challenges in maintaining the interest of program participants. This research provides important input for related parties in increasing the effectiveness and sustainability of digital literacy programs in Ciamis Regency and provides a basis for further research in this field.